R3-306_Ingkiriwang Pelaksanaan Abdimas Edukasi Manajemen Emosi Kejiwaan Bagi Masyarakat di Kelurahan Warakas Tanjung Priok Jakarta - dr. Elly Ingkiriwang, Sp. KJ; Melitina Tecoalu; Fushen Fushen; Hery Winoto Tj; Daud Setiawan; Olga Adjiputro; Fredella Colline; Dwi Aprillita (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Kristen Duta Wacana, 2022)
The long Covid-19 pandemic is still not considered complete in Indonesia. Although there are positive impacts that appear in people's lives, such as the closer relationships within family members because all activities are carried out from home, such as work from home and study from home. But on the other hand, the continuity of this pandemic has had a negative impact on people's lives, especially in the economic field. The inability of the community to deal with economic changes can be one of the triggers for the turmoil of psychological emotions in a person in society. If our mental emotional turmoil is not immediately addressed, the possibility of causing depression and mental disorders can arise which can result in disruption of the country's economy. Because to be able to run well the country's economy requires human resources who are physically and spiritually healthy, starting from a small environment in society. To anticipate this, it is necessary to pay attention to the education sector, in this case Higher Education. The contribution that can be given by the University is to provide services in the form of community service through the provision of counselling in the form of educational information that aims to provide provisions for the community to be ready to face the economic changes that are still ongoing today. The Faculty of Medicine and Health Sciences (FKIK) and the Faculty of Economics and Business (FEB) UKRIDA implement their knowledge according to their competencies to fulfill one of the obligations of the Tridharma of Higher Education, namely by carrying out community service activities.